EFFECT OF ONLINE MARKETING COMMUNICATIONS, CONSUMER PREFERENCES, CONSUMER NEEDS ON PURCHASE BEHAVIOR AND THEIR IMPACT ON PURCHASE DECISIONS (Survey on the Tokopedia and Shopee Online Shop consumers in Bandung) - Munandar, Dadang; Assaf, Rizka Aula; Putri, Sheila Kurnia (Jurnal Soshum Insentif, 2024)
The aim of this research is to study the effect of Online Marketing Communication, Consumer Preferences, and Consumer Need as mediated by Purchase Behavior on Purchase Decision. As many as 100 Tokopedia and Shoppe consumers in Bandung are chosen as the respondents using the purposive method. This research employs quantitative approach by using survey method. The data is analyzed using the mediation analysis technique from the Process Andrew Hayes Software. Research findings are: first, Direct and indirect effect of Online Marketing Communication, Consumer Preferences, and Consumer Need as mediated by Purchase Behavior on Purchase Decision falls into moderate category; second, The determinant factors of Purchase Decision as mediated by Purchase Behavior are affected by 1) Consumer Need; 2) Consumer Preferences and 3) Online Marketing Communication; third, Online Marketing Communication affects significantly on Purchase Decision as mediated by Purchase Behavior. Fourth, Consumer Preferences affect significantly on Purchase Decision as mediated by Purchase Behavior; and fifth, Consumer Need affects significantly on Purchase Decision as mediated by Purchase Behavior.